Malaysia heritage and cultural landmark through embroidery art - Zainun, Norzaleha; Mohamad, Zolina; Talib, Lili Nieta; Mohd Rafee, Mohd Radzuan (2024)
Embroidery known as the art of decorating material primarily on fabric basically by using needle and thread. The used of various types of thread, beads and wires create fascinating textures and colors of modern embroidery that is just not for clothing but also home furnishing object. Fashion Department Universiti Teknologi MARA (UiTM), Perak Branch, Seri Iskandar Campus offers Basic Embellishment subject specially designed for semester three students to explore the creative territory of embroidery art. Through the years, various theme is chosen for embroidery final projects such as landscape, artwork, cartoon, organic and geometric motifs and more. One of the intriguing and challenging theme embroidery project is to develop thematic subject that encompasses Malaysia local heritage and cultural landmark